97.5k views
4 votes
Evaluate x(–y + z) for x = 5, y = 9, and z = 1. 46 –44 –40 50

1 Answer

1 vote

Answer:

-40

Explanation:

We replace x with "5", y with "9", and z with 1, in the algebraic expression:


x(-y+z).

The replacing results as: 5 (-9+1)

Please notice that we need to first solve the combining of numbers inside the parenthesis (the grouping symbol), and then use the implicit multiplication by "5" (multiplying factor outside the parenthesis). Also recall the laws of multiplication of signed numbers, in particular that which tells us that the product of a positive number times a negative number results in a negative number. The full process is shown below:


x(-y+z)\\5*(-9+1)=\\=5*(-8)=\\=-40

User Eugene Barsky
by
5.2k points